MARK2 regulates C9orf72 repeat–associated non-AUG translation - Yu-Ning Lu; Xiangning Li; Lindsey Hayes; Xiao-Feng Zhao; Jiou Wang (Proceedings of the National Academy of Sciences, 2025)
Protein homeostasis is exquisitely regulated through processes involving protein synthesis essential for cellular health and disease prevention. Repeat-associated non-AUG (RAN) translation at expanded GGGGCC repeats in the C9orf72 gene produces dipeptide repeat (DPR) proteins that are implicated in amyotrophic lateral sclerosis and frontotemporal dementia (C9-ALS/FTD). However, the mechanisms promoting this noncanonical translation remain incompletely understood. Here, we identify microtubule affinity-regulating kinase 2 (MARK2) as a key eIF2α kinase that enhances RAN translation under proteotoxic stress. We show that MARK2-eIF2α signaling, activated by misfolded proteins including DPRs and TDP-43, is upregulated in C9-ALS patient tissues. Loss of MARK2 significantly suppresses RAN translation in reporter cells, patient-derived neurons, and a mouse model and confers neuroprotection under proteotoxic conditions. These findings position MARK2 as a critical stress-sensing cytosolic regulator that promotes repeat-associated noncanonical translation and associated toxicity.